Thermally Induced Synthesis of Anthracene‐, Pyrene‐ and Naphthalene‐Fused Porphyrins - Dr. Joffrey Pijeat; Léo Chaussy; Roxanne Simoës; Dr. Jacopo Isopi; Prof. Dr. Jean‐Sébastien Lauret; Prof. Dr. Francesco Paolucci; Prof. Dr. Massimo Marcaccio; Dr. Stéphane Campidelli (ChemistryOpen, 2021)
Abstract The synthesis of π‐extended porphyrins containing anthracenyl moieties still represents an important challenge. Here, we report on the synthesis of a series of unsubstituted naphthyl‐, pyrenyl‐ and anthracenyl‐fused zinc porphyrin derivatives. To this aim, meso‐substitued porphyrins are synthesized and the fusion of the PAHs (Polycyclic Aromatic Hydrocarbon) on the β‐positions are performed through thermally induced dehydro‐aromatization. The fused zinc‐porphyrin derivatives are fully characterized and their optical absorption and photoluminescence properties are reported. We also demonstrate that zinc can be removed from the porphyrin core, giving rise to pure C, H, N materials. This work constitutes the first step towards the synthesis of the fully‐fused tetra‐anthracenylporphyrin.